Pengaruh Rebusan Daun Seledri terhadap Tekanan Darah pada Lansia Penderita Hipertensi Di Desa Panican Kecamatan Kemangkon Kabupaten Purbalingga - Ekaputri, Rahmadani Widya; Julianto, Eko; Puspasari, Fida Dyah (SAMODRA ILMU: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2025)
Background: Hypertension is one of the most common cardiovascular diseases in the elderly. Herbal therapy such as celery (Apium graveolens) decoction is believed to reduce blood pressure. Objective: This study aimed to determine the effect of celery decoction on blood pressure in elderly patients with hypertension. Method: This research used a descriptive case study design with one respondent, a 67-year-old hypertensive patient. The intervention was giving 200 ml of celery decoction every morning after meals for 3 days. Data collection was conducted through interviews, observations, and blood pressure measurements using a digital sphygmomanometer. Results: The average systolic blood pressure showed a slight decrease, while diastolic blood pressure increased. Conclusion: Celery decoction may reduce systolic blood pressure, although the increase in diastolic pressure should be considered cautiously.